A successful search for new, efficient, and silver-free manufacturing processes for key platinum(ii) intermediates applied in antibody–drug conjugate (ADC) production. Issue 7 (5th February 2020) - Merkul, Eugen; Sijbrandi, Niels J.; Aydin, Ibrahim; Muns, Joey A.; Peters, Ruud J. R. W.; Laarhoven, Paul; Houthoff, Hendrik-Jan; van Dongen, Guus A. M. S.
Abstract : A silver-free amination procedure was developed to obtain an important class of Pt(II) complexes as direct precursors for antibody-drug conjugates. Abstract : A silver-free amination procedure, here called "complexation", was developed to obtain a class of Pt(ii ) complexes bearing a payload (such as a diagnostic or a therapeutic moiety). These complexes are crucial intermediates for the efficient development and production of antibody–drug conjugates (ADCs) based on a novel Pt(ii )-based linker technology. We termed this metal–organic linker, [ethylenediamineplatinum(ii )] 2+, " Lx "®. The present, newly developed procedure is a greener alternative for the classically applied activation reaction of Pt-halido complexes with silver salts, followed by amination. The crucial finding is that the leaving ligand of the classical process, chloride, can now be replaced by its higher homologue iodide. This not only decisively improved the manufacturing process of the intermediate, but also was found to be key to a more efficient conjugation procedure, i.e. a subsequent step in which this intermediate is coupled to an antibody. The new process allowed upscaling to be readily realized and the desired intermediate was successfully manufactured on a multigram scale. The obtained Ag-free procedure can be generalized and has a great potential to be applied for other Pt(ii ) complexes of high importance, such as anti-cancer therapeutics.